Preparation and properties of colloidal particles. Silica on yttrium iron garnet - Godoi, R. H.M. [UNESP]; Jafelicci, M. [UNESP]; Portillo, Joaquim (My University, 2000)
Various properties of particles can be altered by coating them with a layer of different chemical composition. Yttrium iron garnet (YIG) particles has been coated with silica for control of their sintering, corrosion resistance, and stabilization of magnetic properties. This silica cover was obtained by hydrolysis of tetraethylorthosilicate (TEOS) in 2-propanol. This material was characterized by transmission (TEM) electron microscopy, (XEDS) X-ray energy-dispersive spectrometry, (XPS) X-ray photoemission spectroscopy and (VSM) vibrating sample magnetometry. YIG was heterocoagulated by silica as indicated by TEM micrographies. XPS measurements indicated that only binding energy for silicon and oxygen was found on the silica shell, which confirms that the YIG was covered. The values of the saturation magnetization differ from the heterocoagulated system to well-crystallized YIG. © 2000 Materials Research Society.